Volume 1: Low/Intermediate-Level Radioactive Waste Management; Spent Fuel, Fissile Material, Transuranic and High-Level Radioac 2013
DOI: 10.1115/icem2013-96275
|View full text |Cite
|
Sign up to set email alerts
|

Review of Passive Corrosion Studies of Carbon Steel in Concrete in the Context of Disposal of HLW and Spent Fuel in Belgium

Abstract: The Supercontainer (SC) design is the preferred option for the final disposal of high level nuclear waste and spent fuel in Belgium. The SC consists of a carbon steel overpack surrounded by a very thick concrete buffer, contained within a stainless steel envelope. In this highly alkaline environment of the annulus and under normal conditions (without the ingress of aggressive species), the carbon steel overpack will be protected by a passive oxide film, which is believed to result in very low and almost neglig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The overpack with a lifetime about 100,000 years will prevent the waste glass from being contacted by the cementitious pore water at least during the thermal phase (about 600 years). Once the overpack will be locally perforated, cementitious pore water will contact vitrified waste (Kursten et al, 2013). Very few glass alteration studies have been reported for hyperalkaline media.…”
Section: Glass Dissolution In Alkaline Solutionmentioning
confidence: 98%
“…The overpack with a lifetime about 100,000 years will prevent the waste glass from being contacted by the cementitious pore water at least during the thermal phase (about 600 years). Once the overpack will be locally perforated, cementitious pore water will contact vitrified waste (Kursten et al, 2013). Very few glass alteration studies have been reported for hyperalkaline media.…”
Section: Glass Dissolution In Alkaline Solutionmentioning
confidence: 98%
“…The results from the cells containing steel wires are adjusted by deducting any pressure fluctuations that occur in the control cells and are normalised to standard temperature and pressure. [ 26–30 ] The setup of the barometric gas cell measurements is shown in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
“…The tensile specimens are strained at a constant slow strain rate of 5 × 10 −7 s −1 at open‐circuit potential (OCP). [ 27,37–40 ]…”
Section: Methodsmentioning
confidence: 99%
“…By measuring the height of the mercury, it was possible to calculate the volume of gas produced and hence to derive the corrosion rate (based on the formation of magnetite as the final corrosion product). The results were corrected for temperature and external atmospheric pressure fluctuations [14][15][16].…”
Section: Anaerobic Uniform Corrosion Studiesmentioning
confidence: 99%